2007
DOI: 10.1525/aeq.2007.38.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Creating Classroom Cultures: One Teacher, Two Lessons, and a High‐Stakes Test

Abstract: Using activities as its analytic focus, this article compares the classroom cultures of two reading lessons taught by the same teacher. One was from a regular reading class and the other from a reading intervention class that was designed to help students pass the high-stakes state assessment. By developing fine-grained descriptions of classroom activities and participant roles, the article offers educators and policymakers a close look at the ways in which childcentered and test-centered classroom cultures ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 4 publications
1
40
0
Order By: Relevance
“…We draw on activity theory (Engeström, 1987) to establish classroom activities as connected, purpose-driven interactive processes, which calls for close examination of relationships among classroom participants' in-themoment attention and actions, and how that gets contextualized by previous experience and systemic environments. Similar analytical focus on activity has been presented by Valli and Chambliss (2007) in a study of two class periods taught by the same teacher.…”
Section: Theoretical Frameworkmentioning
confidence: 63%
“…We draw on activity theory (Engeström, 1987) to establish classroom activities as connected, purpose-driven interactive processes, which calls for close examination of relationships among classroom participants' in-themoment attention and actions, and how that gets contextualized by previous experience and systemic environments. Similar analytical focus on activity has been presented by Valli and Chambliss (2007) in a study of two class periods taught by the same teacher.…”
Section: Theoretical Frameworkmentioning
confidence: 63%
“…This study (Valli & Chambliss, 2007) indicated that placing emphasis on the earlier standards negatively impacted instruction for ESOL students, as the standards put teachers in a position to lean toward teacher-centered instructional practices. The CCSS standards emphasize the kind of learning that is more conducive to a student-centered classroom; thus, it has been anticipated that teachers shifting to the CCSS would employ more student-centered practices, which are more conducive to the language development and learning needs of ELLs.…”
Section: Foundations For a Student-centered Pedagogymentioning
confidence: 88%
“…Overwhelmingly, these practices pointed back toward a student-centered pedagogy. Valli and Chambliss (2007) suggested that a child-centered pedagogy included such practices as active engagement in reading, writing, listening, and speaking for clear purposes; the use of a wide-range of strategies that allowed students to comprehend and produce texts; development of vocabulary; and respect for students' home language, culture, and prior knowledge. In a child-centered pedagogy, "teachers do more than implement a scripted curriculum.…”
Section: Foundations For a Student-centered Pedagogymentioning
confidence: 99%
See 2 more Smart Citations